Exploring the Drivers and Barriers of Entrepreneurship Among Rural Women and Youths: A Case Study of Chibombo District, Zambia. - MUKWANYA NABUSANGA HAMAYANGWE (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: Entrepreneurship in rural areas plays a pivotal role in fostering economic growth and addressing socio-economic disparities. This study examines the drivers and barriers to entrepreneurship among women and youth in Chibombo District, Zambia.